The Implementation of Media in Teaching and Learning of Physical, Sport, and Health Education Subject - S, Adi; Soenyoto, Tommy; Sulaiman, Sulaiman (Journal of Physical Education and Sports, 2018)
This study aimed at knowing the implementation of media in teaching and learning of physical, sport, and health education (PJOK) subject in State Senior High Schools (SMA Negeri) throughout Bojonegoro Subdistrict. In order to investigate such phenomenon, this study employed descriptive research. Moreover, the researcher used survey method with questionnaire as the instrument for data collection. Meanwhile, the subjects of this study were physical, sport, and health education teachers teaching at High School throughout Bojonegoro Subdistrict as many 4 teachers from four schools. Further, the data collected from the subjects of the study were analyzed by using the technique of descriptive percentage. The results showed that the implementation of the media in teaching and learning of physical, sport, and health education in High School throughout Bojonegoro subdistrict achieved Ã¢â‚¬Å“averageÃ¢â‚¬Â category.